Detection of Urinary Antibodies and Its Application in Epidemiological Studies for Parasitic Diseases - Nagaoka, Fumiaki (Vaccines (Basel), 2021)
For epidemiological studies of infectious diseases, pathogen-specific antibody levels in an area give us essential and appropriate information. The antibodies against pathogens are usually detected in blood, the drawing of which inconveniences people. Collection of blood increases the risk of accidental infections through blood, and it is difficult to obtain the participation of the target populations, especially the younger generation. On the other hand, urine samples, which contain a high enough level of antibodies for ELISA, can be harmlessly and easily collected and therefore have been used for epidemiological studies for diseases. The antibody examination of urine has been used for the epidemiology of parasitic diseases with a high sensitivity and specificity of serum samples. In this paper, we reviewed antibody assays with urine for seven parasitic diseases that urine diagnostic methods have reported in the past, and these are important infections included in NTDs, caused, for example, by Leishmania donovani, Wuchereria bancrofti, Schistosoma japonicum, Paragonimus westermani, Echinococcus granulosus, Echinococcus multilocularis, Strongyloides stercoralis, and Opisthorchis viverrini. The easy and safe urine surveillance system might be an admirable tool for future epidemiological studies for infectious diseases.